Pemberdayaan Kader dalam Pengelolaan Sampah Organik menjadi Media Tanam melalui Pendekatan Community Self Survey di Dusun Druwo, Bantul - Zulfa Hemi Nur Aini; Na’wa Nurmalytasari; Dhiya Khairina Maulida; Heru Subaris Kasjono; Ibnu Rois (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2024)
Organic waste management at the household level remains a critical environmental health challenge, particularly following limitations in landfill capacity. This condition highlights the need for community-based empowerment approaches to enhance independent waste management practices. This community service program aimed to improve knowledge, attitudes, skills, and participation of community members in managing organic waste as planting media in Dusun Druwo, Bantul. A participatory community-based approach was applied through four stages: education (L1), Community Self Survey (L2), training and demonstration (L3), and cadre-led dissemination (L4). Outcome measurements included pretest–posttest assessment, skill observation, and monitoring of cadre participation. The results showed improvements in knowledge and attitudes, reflected by increased awareness of improper waste disposal behavior (98% to 100%), perceived ease of independent waste management (89% to 95%), and preference for self-managed waste processing over direct disposal (73% to 78%). Observations also indicated improved practical skills in producing planting media from organic waste. Cadre participation in dissemination was implemented at the community level, although not evenly across all areas. This program contributed to enhancing community capacity in organic waste management and initiated positive behavioral changes toward environmentally sustainable practices.